2006
DOI: 10.2174/157340506777934552
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Moving Blood Volume Measurement Using Power Doppler Ultrasound as an Estimation of Fetal Organ Blood Perfusion

Abstract: Fractional moving blood volume (FMBV) estimated using power Doppler ultrasound (PDU) is a sensitive technique to detect slow blood movement. However, several factors as; depth, attenuation and blood characteristics can affect the PDU signals. The aim of this study was to standardized and validate the FMBV measurement compensating for the factors that can affect the final results, in order to accurate estimate blood movement in a specific region of interest (ROI) of fetal organs as an estimation of blood perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The first is that FMBV is an indirect estimate of tissue blood perfusion. However, the technique has shown a strong correlation with ‘gold standards’ in experimental conditions16 and we have previously shown that brain FMBV can be estimated reliably and consistently in human fetuses17–19. Our results are consistent with those of Dubiel et al 28, who also reported that growth‐restricted fetuses have increased brain power Doppler signals, although these authors did not evaluate FMBV or the existence of regional variations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The first is that FMBV is an indirect estimate of tissue blood perfusion. However, the technique has shown a strong correlation with ‘gold standards’ in experimental conditions16 and we have previously shown that brain FMBV can be estimated reliably and consistently in human fetuses17–19. Our results are consistent with those of Dubiel et al 28, who also reported that growth‐restricted fetuses have increased brain power Doppler signals, although these authors did not evaluate FMBV or the existence of regional variations.…”
Section: Discussionsupporting
confidence: 90%
“…As described previously19, the regions of interest (ROIs) were delimited offline as follows: frontal, in an anterior mid‐sagittal view of the fetal head, delimited anteriorly by the internal wall of the skull, posteriorly by an imaginary line drawn at 90° at the level of the origin of the anterior cerebral artery and parallel to an imaginary line in the front of the face, and inferiorly by the base of the skull (Figure 1a); complete mid‐cerebral, in a mid‐sagittal plane delimited by the complete internal wall of the fetal skull (Figure 1b); basal ganglia in a mid‐parasagittal view, delimited by the head, body and tail of the caudate nucleus and inferiorly by the lenticular nucleus (Figure 1c), and the cerebellum delimited anteriorly by the base of the cerebellar hemispheres, approximately at the level of the junction of the posterior cerebral arteries with the posterior communicating arteries, and posteriorly by the fetal skull (Figure 1d). Pixels containing color PDU data within the ROIs were used for FMBV calculation according to previously described methodology17–19. The mean FMBV from all 10 images was considered as the representative value for each fetus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of the limitations of this study; placental 3D indices generated by the VOCAL histogram could have been affected by several parameters of the machine such as gain, power, pulse repetition frequency, wall motion filter, signal rise, and persistence . Because of its relative simplicity, low intra‐observer and interobserver variability and vast experience, we preferred to use the VOCAL method for estimating the placental blood flow and did not use additional standardization techniques such as the ‘fractional moving blood volumes in which measurement are scaled to the maximum potential detectable amplitude with 100% blood. Also, we could not use transvaginal transducer for minimizing signal attenuation because of the advanced gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Each image was rendered and pixels containing color information within the ROI were selected for analysis (Figure 1c). FMBV was calculated according to the methodology described previously, using a double normalization process19 (Figure 1d).…”
Section: Methodsmentioning
confidence: 99%